Fear-Avoidance Beliefs for Physical Activity Among Chronic Low Back Pain: A Multicenter Cross-Sectional Study - Yihunie M; Abich Y; Demissie SF; Kassa T; Ranganathan P; Janakiraman B (Journal of Pain Research, 2023)
Mulualem Yihunie1 ,† Yohannes Abich,1 Solomon Fasika Demissie,1 Tesfa Kassa,1 Parthasarathy Ranganathan,2 Balamurugan Janakiraman3 1Department of Physiotherapy, School of Medicine, College of Medicine and Health Sciences, University of Gondar, Gondar, Ethiopia; 2Faculty of Physiotherapy, Meenakshi Academy of Higher Education and Research (MAHER), Chennai, India; 3Department of Research and Faculty of Physiotherapy, Meenakshi Academy of Higher Education and Research (MAHER), Chennai, India†Mulualem Yihunie passed away in May 2022Correspondence: Yohannes Abich, Department of Physiotherapy, School of Medicine, College of Medicine and Health Sciences, University of Gondar, PO Box: 196, Gondar, Ethiopia, Email yohannesabich@yahoo.comBackground: Among different psychological predictors of outcome in low back pain (LBP) adults, the negative influence of fear-avoidance beliefs in physical activity is an area of research attention. However, there is a lack of evidence on the burden of fear avoidance about physical activity among chronic LBP adults in Ethiopia.Objective: To describe fear-avoidance beliefs about physical activity and explore its association with socio-demographic and clinical factors among low back pain patients attending physiotherapy treatment in 3 Amhara regional comprehensive hospitals.Methods: A multi-center cross-sectional study was conducted and adults with chronic LBP (n = 263) participated. Data were collected by face-to-face interview using the modified Fear-Avoidance Belief Questionnaire about Physical Activity (mFABQ-PA) tool. Multivariable logistic regression at a p-value < 0.05 significance level was used to identify predictors of fear-avoidance beliefs about physical activity.Results: Among the 263 participants, 113 subjects (43%, 95% CI (36.9– 49.0)) reported a higher cut-off (> 15) mFABQ-PA. The logistic regression model demonstrated that LBP adults with a higher mFABQ-PA score were more likely to be urban residents (AOR 2.75, 95% CI (1.32, 5.88)), and ADL-related LBP (AOR 1.97 95% CI (1.18, 3.29)). The clinical-specific factor indicative of a higher cut-off score of mFABQ-PA was using analgesic medications (AOR 2.00, 95% CI (1.19, 3.37)). The model fit was 0.21 and 0.11 (R2 = Nagelkerke’s, Cox & snell respectively).Conclusion: High fear avoidance beliefs about physical activity in adults with low back pain were found and associated with residence, work, and medication intake. These findings might urge the researchers to explore further associations and assist clinicians in choosing subgroups to use behavioral therapy and graded exposure to physical activity.Keywords: avoidance behavior, fear-avoidance beliefs, low back pain, physical activity